Clinical Characteristics and Predictors of Outcomes of Hospitalized Patients With Coronavirus Disease 2019 in a Multiethnic London National Health Service Trust: A Retrospective Cohort Study. (7th August 2020) - Perez-Guzman, Pablo N; Daunt, Anna; Mukherjee, Sujit; Crook, Peter; Forlano, Roberta; Kont, Mara D; Løchen, Alessandra; Vollmer, Michaela; Middleton, Paul; Judge, Rebekah; Harlow, Christopher; Soubieres, Anet; et al.
Abstract: Background: Emerging evidence suggests ethnic minorities are disproportionately affected by coronavirus disease 2019 (COVID-19). Detailed clinical analyses of multicultural hospitalized patient cohorts remain largely undescribed. Methods: We performed regression, survival, and cumulative competing risk analyses to evaluate factors associated with mortality in patients admitted for COVID-19 in 3 large London hospitals between 25 February and 5 April, censored as of 1 May 2020. Results: Of 614 patients (median age, 69 [interquartile range, 25] years) and 62% male), 381 (62%) were discharged alive, 178 (29%) died, and 55 (9%) remained hospitalized at censoring. Severe hypoxemia (adjusted odds ratio [aOR], 4.25 [95% confidence interval CI, 2.36–7.64]), leukocytosis (aOR, 2.35 [95% CI, 1.35–4.11]), thrombocytopenia (aOR [1.01, 95% CI, 1.00–1.01], increase per 10 9 decrease), severe renal impairment (aOR, 5.14 [95% CI, 2.65–9.97]), and low albumin (aOR, 1.06 [95% CI, 1.02–1.09], increase per gram decrease) were associated with death. Forty percent (n = 244) were from black, Asian, and other minority ethnic (BAME) groups, 38% (n = 235) were white, and ethnicity was unknown for 22% (n = 135). BAME patients were younger and had fewer comorbidities. Although the unadjusted odds of death did not differ by ethnicity, when adjusting for age, sex, and comorbidities, black patients were at higher odds of death compared to whites (aOR, 1.69 [95% CI, 1.00–2.86]). This association was stronger when further adjusting for admission severity (aOR, 1.85 [95% CI, 1.06–3.24]). Conclusions: BAME patients were overrepresented in our cohort; when accounting for demographic and clinical profile of admission, black patients were at increased odds of death. Further research is needed into biologic drivers of differences in COVID-19 outcomes by ethnicity. Abstract : Fever, hypoxemia, thrombocytopenia, hypoalbuminemia, leukocytosis, and renal impairment on admission are associated with increased odds of hospital mortality among COVID-19 patients. Black ethnic background is an independent predictor of hospital mortality, after adjusting for demographic and clinical confounders.